Noise and vibration mitigation for rail transportation systems proceedings of the 11th International Workshop on Railway Noise, Uddevalla, Sweden, 9-13 September 2013 - Nielsen, Jens C. O. (Springer Berlin Heidelberg, 2015)
The book reports on the 11th International Workshop on Railway Noise, held on 9 - 13 September, 2013, in Uddevalla, Sweden. The event, which was jointly organized by the Competence Centre Chalmers Railway Mechanics (CHARMEC) and the Departments of Applied Mechanics and Applied Acoustics at Chalmers University of Technology in Gothenburg, Sweden, covered a broad range of topics in the field of railway noise and vibration, including: prospects, legal regulations and perceptions; wheel and rail noise; prediction, measurements and monitoring; ground-borne vibration; squeal noise and struct.